The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15252/embj.2020105561
|View full text |Cite
|
Sign up to set email alerts
|

BCL‐XL exerts a protective role against anemia caused by radiation‐induced kidney damage

Abstract: Studies of gene-targeted mice identified the roles of the different prosurvival BCL-2 proteins during embryogenesis. However, little is known about the role(s) of these proteins in adults in response to cytotoxic stresses, such as treatment with anti-cancer agents. We investigated the role of BCL-XL in adult mice using a strategy where prior bone marrow transplantation allowed for loss of BCL-XL exclusively in non-hematopoietic tissues to prevent anemia caused by BCL-XL deficiency in erythroid cells. Unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The loss of BCL-XL causes aberrant apoptosis in postmitotic immature neurons of the developing brain, spinal cord, and dorsal root ganglion, demonstrating its essential role in the survival of these cell populations [28]. Conditional gene deletion studies have shown that in adult mice BCL-XL is critical for erythropoiesis and the survival of certain cell populations in the kidney [29].…”
Section: The Role Of Pro-survival Bcl-2 Proteins In Organismal Develo...mentioning
confidence: 99%
“…The loss of BCL-XL causes aberrant apoptosis in postmitotic immature neurons of the developing brain, spinal cord, and dorsal root ganglion, demonstrating its essential role in the survival of these cell populations [28]. Conditional gene deletion studies have shown that in adult mice BCL-XL is critical for erythropoiesis and the survival of certain cell populations in the kidney [29].…”
Section: The Role Of Pro-survival Bcl-2 Proteins In Organismal Develo...mentioning
confidence: 99%
“…BCL2 is reported to contribute to the development and homeostasis of the mouse epidermis [ 1238 ]. Along similar lines, MCL1 and BCL- X L play roles in the development and homeostasis of several tissues including the myocardium [ 1239 , 1240 ], the CNS [ 148 , 1241 1248 ], the hepatic parenchyma [ 298 , 845 , 1249 1251 ], vascular endothelium [ 1252 ], thymic epithelium [ 1253 ], as well as the intestinal [ 1254 ], mammary [ 1255 , 1256 ], lung [ 1257 ] and renal [ 277 ] epithelium.…”
Section: Intrinsic Apoptosis In Diseasementioning
confidence: 99%
“…Similarly, Z-VAD-FMK is ineffective in mouse models of osmotic nephrosis and contrast-induced acute kidney injury [ 276 ], and this may be linked to the ability of Z-VAD-FMK to inhibit CASP8 (and hence promote necroptosis). Finally, acute loss of BCL-X L in all tissues of adult mice, except for hematopoietic cells, caused severe renal tubular degeneration leading to fatal anemia due to the loss of erythropoietin production [ 277 ].…”
Section: Intrinsic Apoptosis In Diseasementioning
confidence: 99%